Cloning and expression of the cloacin DF13/aerobactin receptor of Escherichia coli (ColV-K30). - Krone, W J (1983)
A DNA fragment derived from the ColV-K30 plasmid and coding for both sensitivity to cloacin DF13 and Fe3+-aerobactin uptake was cloned into pBR322. The cloned fragment coded for two polypeptides with molecular masses of 74,000 (the cloacin DF13/aerobactin receptor protein) and 50,000 daltons, respectively. When grown with sufficient iron, cells harboring pFS8 (with this fragment) possessed about 10 times as many receptor protein molecules as compared with cells of Escherichia coli (ColV-K30). The synthesis of the receptor protein specified by pFS8, however, was independent of the availability of iron, in contrast to strains harboring the intact ColV-K30 plasmid. Aerobactin was taken up but not synthesized by cells harboring pFS8. No growth occurred when iron-starved cultures of these cells were incubated with Fe3+-aerobactin, suggesting that expression of other ColV-K30-encoded genes is necessary to remove the iron from the Fe3+-aerobactin complex.